Subarachnoid haemorrhage: older patients have low cerebral blood flow. Issue 6349 (23rd October 1982) - Meyer, C H; Lowe, D; Meyer, M; Richardson, P L; Neil-Dwyer, G
Abstract : Daily estimations of hemispheral cerebral blood flow using the xenon-133 inhalation technique was made in 116 patients during the first three weeks after subarachnoid haemorrhage. The patients' cerebral perfusion on average remained less than the normal perfusion expected for their age (based on a single estimation of cerebral blood flow in 67 volunteers). On each separate day after subarachnoid haemorrhage cerebral blood flow was inversely related to the patient's age. Older patients seem especially at risk of developing cerebral ischaemia after subarachnoid haemorrhage. The clinical outcome was more often unfavourable in older patients–that is, in those who tended to have the lowest cerebral blood flow. Present results support the view that episodes of low cerebral blood flow lead to a poor outcome after subarachnoid haemorrhage. Because of the risk of inducing cerebral ischaemia great care should be exercised by physicians administering hypotensive drugs to older patients after subarachnoid haemorrhage.